Factors with conformational effects on haemostatic serpins: Implications in thrombosis - Hernández-Espinosa, David; Ordóñez, Adriana; Vicente, Vicente; Corral, Javier (Thrombosis and Haemostasis, 2007)
Serpins are key actors of systems involving proteolytic reactions, such as the haemostatic system, as they are irreversible suicide inhibitors of serine proteases. The structural flexibility and physical properties of serpins that are required for their efficient inhibitory mechanism also make them especially vulnerable to even minor factors that induce conformational changes in the native form of these molecules, leading to a number of inactive conformations, such as latent, cleaved or polymers. Increasing numbers of conformational mutations affecting haemostatic serpins, mainly antithrombin, the main endogenous anticoagulant, have been described. These mutations cause circulating deficiencies of the molecules, in most cases due to intracellular retention, which may be associated with a hyper-coagulable state. Indeed, conformational mutations in antithrombin have been identified in patients with severe venous thrombosis,which has led to the hypothesis that these disorders might be included in the group of conformational diseases. Moreover,we have recently demonstrated that other factors,including both drugs,such as the treatment with L-asparaginase,or environmental factors, such as high temperatures or hyperlipidemia, may also have conformational consequences on hepatic antithrombin,thus resulting in intracellular aggregation and plasma deficiency, which may increase the risk of thrombosis. In this study,we review the causes of deficiency of haemostatic serpins that may be explained by conformational mechanisms, and their association with an increased risk of venous thrombosis.
Keywords: Antithrombin; SERPINs; venous thrombosis; liver